Fifty years of Lithuanian school mathematical olympiads - Kašuba, Romualdas; Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2001)
In the paper the importance of the mathematical olympiads for the general development as well as for the actual state of education and training of mind and related problems are discussed. A review of the local net of Lithuanian olimpiads is made and especially the last achievments of the Lithuanian high school and University students in the World olympiads are analyzed.